Effectiveness of 8 weeks of Panchakshari mantra chanting on cognitive and psychological parameters in young adults - Anitha Lakshmi; Bhargavi SK; Shashikumar SD; Yashica Gowda R; Sai Sailesh Kumar Goothy; Mukkadan JK (Asian Journal of Medical Sciences, 2024)
Background: It was reported that those who practice chanting of the Shiva panchakshari mantra can overcome stress, attain prosperity, and get stability in life. However, there are no research studies in this area in the PubMed literature to support scientific evidence.